Experimental characterization of picosecond laser interaction with solid targets. - Jung, D; Gizzi, L; Labate, L; Neely, D; Notley, M; Rajeev, P; Roth, M; Gregori, G (2008)
We have characterized the plasma produced by a picosecond laser pulse using x-ray spectroscopy. High-resolution high-sensitivity spectra of K -shell emission from a Ti plasma have been obtained, showing a strong contribution from multiply ionized ions. Hydrodynamic and collisional-radiative codes are used to extract the plasma temperature and density from these measurements. We show that our measurements can provide benchmarks for particle-in-cell (PIC) simulations of preplasma conditions in ultraintense laser-matter interactions.